Emerging Trends in the Development of Chitosan Films for Active Food Packaging - Barleany, Dhena Ria; Sari, Denni Kartika; Lestari, Retno Sulistyo Dhamar (World Chemical Engineering Journal, 2020)
The demand for healthy and safe foods with the minimum use of synthetic materials is increasing very rapidly. Plastic polymers have negative effects on the environment, and great efforts have been made to evaluate the use of various bio-based polymers as alternatives to synthetic plastic packaging. Chitin and chitosan are mostly extracted from crustacean shells or byproducts from processing and handling fish and seafood. As a result, chitosan as a material for food packaging has received much attention and is widely researched because it has unique biological and functional properties. Chitosan for food packaging and food preservation applications can be applied via the method of spraying, immersing, coating, or wrapping films. However, chitosan has several disadvantages including low mechanical properties and high sensitivity to moisture, which are the main limitations for its industrial applications, including food packaging. In this study, the scientific literature of the last 5 years on chitosan-based films for their potential application in the food packaging industry has been extensively reviewed. This review also discussed various strategies that have been implemented to improve the properties of chitosan film, including using plasticizers and cross-linking agents, filling them with nanoparticles, fibers and whiskers and combining them with natural extracts and essential oils as well as with other natural and synthetic ingredients.